Leukemogenic kinase FIP1L1‐PDGFRA and a small ubiquitin‐like modifier E3 ligase, PIAS1, form a positive cross‐talk through their enzymatic activities. Issue 2 (February 2017) - Ibata, Makoto; Iwasaki, Junko; Fujioka, Yoichiro; Nakagawa, Koji; Darmanin, Stephanie; Onozawa, Masahiro; Hashimoto, Daigo; Ohba, Yusuke; Hatakeyama, Shigetsugu; Teshima, Takanori; Kondo, Takeshi
Abstract : Fusion tyrosine kinases play a crucial role in the development of hematological malignancies. FIP1L1‐PDGFRA is a leukemogenic fusion kinase that causes chronic eosinophilic leukemia. As a constitutively active kinase, FIP1L1‐PDGFRA stimulates downstream signaling molecules, leading to cellular proliferation and the generation of an anti‐apoptotic state. Contribution of the N‐terminal FIP1L1 portion is necessary for FIP1L1‐PDGFRA to exert its full transforming activity, but the underlying mechanisms have not been fully characterized. We identified PIAS1 as a FIP1L1‐PDGFRA association molecule by yeast two‐hybrid screening. Our analyses indicate that the FIP1L1 portion of FIP1L1‐PDGFRA is required for efficient association with PIAS1. As a consequence of the association, FIP1L1‐PDGFRA phosphorylates PIAS1. Moreover, the kinase activity of FIP1L1‐PDGFRA stabilizes PIAS1. Therefore, PIAS1 is one of the downstream targets of FIP1L1‐PDGFRA. Moreover, we found that PIAS1, as a SUMO E3 ligase, sumoylates and stabilizes FIP1L1‐PDGFRA. In addition, suppression of PIAS1 activity by a knockdown experiment resulted in destabilization of FIP1L1‐PDGFRA. Therefore, FIP1L1‐PDGFRA and PIAS1 form a positive cross‐talk through their enzymatic activities. Suppression of sumoylation by ginkgolic acid, a small molecule compound inhibiting a SUMO E1‐activating enzyme, also destabilizes FIP1L1‐PDGFRA, and while the tyrosine kinase inhibitor imatinib suppresses FIP1L1‐PDGFRA‐dependent cell growth, ginkgolic acid or siRNA of PIAS1 has a synergistic effect with imatinib. In conclusion, our results suggest that sumoylation by PIAS1 is a potential target in the treatment of FIP1L1‐PDGFRA‐positive chronic eosinophilic leukemia. Abstract : A leukemogenic fusion kinase FIP1L1‐PDGFRA co‐localizes with a SUMO E3 ligase PIAS1 in nucleus. PDGFRA‐C lacking the FIP1L1 portion mainly locates in cytoplasm.